Students' Nutrition Knowledge and Teachers' Perceptions of Integrating Nutrition Messages into Junior High School Curriculum - Emilia, Esi; Mulyana, Rachmat; Permatasari, Tyas; Pasca Rassy, Regania; Mutiara, Erli (Jurnal Gizi dan Pangan, 2022)
This study aimed to measure nutritional knowledge and observe teachers' perceptions of delivering nutrition messages through an e-module within the junior high school curriculum. This study was conducted at SMPN 35 Medan and employed the quasi-experimental approach, and a one-group pretest-posttest design was used. This study’s population was students in grades 7 and 8. The minimum sample size was 102 students after adding 10% of the total sample size. Teachers' perceptions were taken from four subject teachers. Data were collected using a questionnaire survey and an interview. A focus group discussion was conducted with the teachers to gather information about their perceptions of using an e-module to deliver nutrition messages at school. The data were analyzed using the Wilcoxon test. The results showed that the student's average total knowledge score before receiving the nutrition education intervention was 22.66. It increased to 26.48 after students received the intervention. Teachers used the e-module to deliver content learning about nutritional messages in schools and employed the e-module to deliver the relevant subject matters of nutrition messages at school. The teachers realized the importance of delivering nutrition messages to the students. The e-module could broaden the teachers’ horizons as they came to realize that nutrition messages could be delivered through various subjects. They initially believed that nutrition messages could only be taught in the subject of natural sciences. However, they discovered that nutrition messages could also be delivered in other subjects, such as mathematics, crafts, and physical education.